Comparative clinical effectiveness and safety of super bioavailable itraconazole and conventional itraconazole in management of dermatophytosis: a retrospective data analysis - Mahajan, Harshal; Dhoot, Dhiraj; Deshmukh, Gaurav; Barkate, Hanmant (International Journal of Research in Dermatology, 2021)
Background: A newer itraconazole formulation i.e., super bioavailable itraconazole has been launched recently in India which is claimed to overcome all the pharmacokinetic challenges faced with conventional itraconazole. The present retrospective data analysis was undertaken to evaluate the effectiveness and safety of super bioavailable itraconazole in comparison with conventional itraconazole in the treatment of dermatophytosis in Indian patients. Methods: The present multi-centric, retrospective data analysis was done at 12 dermatological centers across India from July 2020 to December 2020. Medical records of patients of dermatophytosis, who were prescribed with either super bioavailable itraconazole 50 mg twice daily for four weeks or conventional itraconazole 100 mg twice daily for four weeks were included in the study. Results: 56% patients (n=30) in super bioavailable itraconazole group achieved complete clearance of their symptoms (cured) compared to only 34% patients (n=17) in conventional itraconazole group and this difference was statistically significant (p=0.02). Significantly more patients achieved complete clearance of their lesions in super bioavailable itraconazole-37 patients (69%) compared to conventional itraconazole group-25 patients (49%) at the end of 4 week therapy (p=0.04). The difference in total symptom score (∆TSS) in super bioavailable itraconazole group was more (5.81) as compared to conventional itraconazole group (4.75) (p=0.09). Both the treatment were well tolerated. Conclusions: From the findings of the present study, super bioavailable itraconazole was more effective with similar safety profile as compared to conventional itraconazole in the treatment of dermatophytosis.